Questioning and discursive rationalization of productive processes in organizations (Journal of Information Systems and Technology Management, 2010)
In this article, the academic questioning and rationalization of productive processes in organizations are discussed. The organizational dynamics in Luhmann's theory of systems that emphasize the relationship of the system with its surroundings is also discussed. This theory allows for the analysis of organizations complexity, including their dynamics and processes.The concept of organizational autopoiesis is highlighted in this study. The discussion of quality improvement and innovation of production processes is based on pedagogical issues of the organizations. The possibilities of Habermas' communicative action theory is discussed, especially in the form of discursive rationalization of complex organizational processes In conclusion, discursive rationalization may be important to build effective and integrated organizations through an ethical and sympathetic basis.